Case report: Minimal manifestations of mucous membrane pemphigoid in a young adult - Schauer, Franziska; Casetti, Federica; Kiritsi, Dimitra (Frontiers in Medicine, 2022)
A male patient presented in our department at the age of 23, suffering from recurrent, painful erosions in the urethral outlet area. In closer clinical examination gingival erosions, primarily around the teeth were identified as well. Indirect immunofluorescence on salt split skin with epidermal IgG deposition and positive anti-BP230 IgG ELISA diagnostics hinted towards the presence of mucous membrane pemphigoid (MMP). Direct immunofluorescence from oral mucosa confirmed the diagnosis. MMP in young adulthood is an underdiagnosed disease and latency of diagnosis was around 4 years in our case. Treatment with systemic glucocorticosteroids and dapsone led to clinical remission, prohibiting the development of MMP manifestations in further organs and complications associated with the disease, e.g. scar formation and miction problems.